Evaluation of old store-and-release covers on discard dumps and backfilled pits to improve and predict their performance for rehabilitated mines at Mpumalanga Highveld, South Africa - Van Schalkwyk, Roeline (Stellenbosch : Stellenbosch University, 2021)
Thesis (PhDAgric)--Stellenbosch University, 2021.